Cover Image. (16th December 2022) - Unknown
Abstract : The first fifty years have passed since Colin Baird's pioneering paper in 1972 ‐ now starts the next fifty by Henrik Ottosson, Bo Durbeej and Miquel Solà. Cover image by Sílvia Escayola